Transitivity in the text of Indonesian presidential candidates debate - Setiawan, Irma; Laksana, I Ketut Darma; Mahyuni, -; Udayana, I Nyoman (International research journal of management, IT and social sciences, 2018)
The presidential debate is a fundamental part of a sort of presidential election events worldwide. A number of developing countries with a presidential system of government always carry out hearing, listening and tracking the vision and mission of the nation and country. This activity is conducted to introduce the presidential candidates and vice presidents to the citizens. For example, the presidential debate in Indonesia raises a variety of social phenomena of language. There are three main factors behind selecting this phenomenon of language at the 2014 presidential debate, namely: empirical, practical, and theoretical as the topic of a study. In order to answer these three phenomena, the researcher focuses on the linguistic exposure system on the Candidate Debate Text (CDT) for the presidential election. This study aims at describing deeply the various aspects of the exposure system of the linguistic experiences of the two presidential candidates of Indonesia in the debate. Moreover, this study intends to describe the scheme and the range or reach of the discussion conducted by two candidates through debate. The theory used as the basic reference of this study is Systematic Functional Linguistics (SFL) articulated by Halliday (1985,1991, 2004, 2014).